Sistem Informasi Pajak Bumi dan Bangunan Berbasis Stand Alone - Kristina Natonis; Maria Adelvin Londa; Melky Radja (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
The problem in this study is that the Land and Building Tax Service at the Potulando Village Office is still manual or conventional, so it requires a lot of place and time in storing data or processing data, besides that the reports produced are inaccurate. The purpose of this research is to design a Stand Alone -Based Land and Building Tax Information System. Sources of data in this study are primary data sources and secondary data sources. This type of research is qualitative while the data collection techniques in this study use three methods, namely, observation, interviews and library studies. The construction of a Stand Alone-Based Land and Building Tax Information System in this study uses Visual Basic.Net . The system development method used in this research is System Development. Life Cycle (SDLC), while The system testing technique in this study uses the Blackbox testing method. The system design in this study uses a use case diagrams, context diagrams, and data flow diagrams. With the existence of a Land and Building Tax Information System , it can improve the tax service process quickly and practically compared to the manual process , facilitate the process of recording taxpayer identity , able to obtain the desired taxpayer data quickly and easily. Facilitate the process of making tax reports , both monthly and annual reports .